THE PEDAGOGICAL VALUE OF THE VIRTUAL CLASSROOM (VC): THE USERS TALK - Sulmont Haak, Lea (2007)
What is the pedagogical value of the Virtual Classroom for the students and for the teachers? This work presents the results of a longitudinal study about the integration of the Virtual Classroom at the university and analyzes, from a comprehensive perspective, the types of uses of the VC in a formal learning environment like at the University, where the presence of the teacher is a must. It sets forth the concept of the pedagogical value understood as the benefit the users perceive from this tool as a means of support in their teaching-learning process. This value can only be recognized when it is used in a concrete experience within a learning situation. For this, the study is structured in four levels of complementary analysis: the evolution of the use of the VC at the UPC, the perception of the use of the ITC’s (Information Technology and Communication) in education, the purposes of the uses of the VC and the perception of the pedagogical value of the VC. Finally, the article discusses how the Virtual Classroom amplifies the pedagogical practice and declares that the sole presence of such technological tool does not necessarily mean an evolution in these practices. Without doubt, the article demands for the renovation of the users’ capabilities.